Prevención del embarazo en adolescentes: factores Socioeconómicos y nivel de conocimiento en pacientes Atendidas en el Hospital Minsa II – 2 Tarapoto, Julio – Diciembre 2015 - Mendoza Mendoza, Maricela (2015)
This research entitled "Adolescent Pregnancy Prevention: socioeconomic factors And knowledge level in patients treated at MINSA II Hospital - 2 Tarapoto, July- December 2015", quantitative, descriptive, correlational, cross, whose sample was 92 pregnant teenagers, I use as the survey methodology and an a questionnaire as A tool. The results were: pregnant adolescents presented as social factors: 87% (80) age 17 to 19 a; 63% (58) cohabitants; 65.2% (60) grade of secondary education and Come from rural areas, 56.5% (52) are Catholic, 52.2% (48) started their sex Between 17-19 to 34.8% (32 ) live with another family. As economic factors: 97.8% (90) a parent working, 93.5% (86) the couple works, 73.9% (68) are economically Dependent on the couple, 56.5% (52) income family ranges in 501-999 soles. The Level of knowledge about pregnancy prevention measures was average 39.1% (36) High 32.6% (30). In conclusion the main socioeconomic factors most influence on the level of Knowledge on prevention of teen pregnancy are: education level (X2 = 8.975; p = 0.0110) type of educational institution (X2 = 10.776; p = 0.0050), Family Income (X2 = 9.961; p = 0.0460) and that the couple work (X2 = 8.147; p = 0.0170)